2007
DOI: 10.1021/np060484y
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Prenylated Stilbenes and Flavonoids from Macaranga alnifolia from the Madagascar Rainforest,1

Abstract: Bioassay-guided fractionation of an extract of the fruit of Macaranga alnifolia from Madagascar led to the isolation of four new prenylated stilbenes, schweinfurthins E-H (1-4), and one new geranylated dihydroflavonol, alnifoliol (5). The known prenylated stilbene, vedelianin (6), and the known geranylated flavonoids, bonanniol A (7), diplacol (8), bonannione A (9) and diplacone (10), were also isolated. All ten compounds were tested for antiproliferative activity in the A2780 human ovarian cancer cell line as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
115
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(127 citation statements)
references
References 31 publications
5
115
0
Order By: Relevance
“…After removing the solvent, the aqueous residue was partitioned in sequence with CHCl 3 and n-BuOH, yielding CHCl 3 and n-BuOH extracts. The two fractions were subjected to a series of chromatographic steps to afford eight new flavonoid derivatives (1-8) and 14 known compounds (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removing the solvent, the aqueous residue was partitioned in sequence with CHCl 3 and n-BuOH, yielding CHCl 3 and n-BuOH extracts. The two fractions were subjected to a series of chromatographic steps to afford eight new flavonoid derivatives (1-8) and 14 known compounds (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
“…The UV absorption at 328 nm was characteristic of a stilbene skeleton. 18 Its IR spectrum displayed the presence of aromatic rings (1606, 1510, and 1466 cm -1 ) and hydroxy functions (3406 cm -1 13 C NMR data of 2 revealed that 2 was similar to 1 except that two meta-coupled doublets at δ 6.33 and 6.56 (1H, d, 1.8, each) could be observed in 2, in place of the symmetrical aromatic proton pattern at δ 6.69 (2H, s)] in 1, suggesting also a stilbene moiety and a deoxotetrahydrochalcone unit in the structure of 2. The complete assignment of the protonated carbon resonances was made using the HSQC spectrum, while analysis of the HMBC and ROESY spectra of 2 confirmed the existence of a stilbene moiety and a deoxotetrahydrochalcone unit in the structure of 2 ( Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In folk medicine, traditional healers use fresh or dried leaves of some Macaranga species to treat swellings, cuts, sores, boils and bruises (Nick et al, 1995). A phytochemical review of literatures indicates the genus Macaranga to be a rich source of the isoprenylated, geranylated and farnesylated flavonoids (Schutz et al, 1995;Jang et al, 2002;Phormmart et al, 2005;Kawakami et al, 2008;Thanh et al, 2012) and stilbenes (Beutler et al, 1998;Yoder et al, 2007;Thanh et al, 2012). Furthermore, more classes of secondary metabolites like terpenes (Salah et al, 2003;Jang et al, 2004;Phormmart et al, 2005;Kawakami et al, 2008), tannins (Lin et al, 1990;Gunawan-Puteri and Kawabata, 2010;Ngoumfo et al, 2008), coumarins (Sutthivaiyakit et al, 2002;Darmawan et al, 2012) and other types of compounds (Ramaiah et al, 1979;Ngoumfo et al, 2008;Matsunami et al, 2009;Zakaria et al, 2010) are known to be isolated from different species of the genus Macaranga.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of phytochemical studies are being carried out on plants belonging to the genus Macaranga due to their various traditional uses. Thus, the isolated natural products from this genus have been reported to display interesting biological activities including antitumor (Kaaden et al, 2001;Yoder et al, 2007;Zakaria et al, 2012), antioxidant (Sutthivaiyakit et al, 2002;Phormmart et al, 2005;Matsunami et al, 2009), antimicrobial (Salah et al, 2003;Lim et al, 2009) and anti-inflammatory (Jang, et al, 2002). This is a resourceful area of research as many species of Macaranga are used in traditional medicine as well as exhibits various pharmacological properties while their chemistry indicates varied chemical structures.…”
Section: Introductionmentioning
confidence: 99%